Compartment Syndrome Secondary to Intraosseous Access Abutting Tibial Stem Cement Mantle of a Total Knee Arthroplasty: A Case Report. Issue 1 (January 2022) - Chughtai, Morad; Pang, Aaron; Khan, Taiba; Cantrell, William C.; Mesko, Nathan W.; Kamath, Atul F.
Abstract : Case: A 79-year-old man 6 days status-post left total knee arthroplasty (TKA) presented to our institution from an outside hospital (OSH) after a suspected STEMI and ventricular fibrillation arrest. At the OSH, intraosseous (IO) access was placed in his right tibia. Orthopaedics was consulted for compartment syndrome at the IO access site. X-rays demonstrated this was secondary to the IO access abutting the cement mantle of a stemmed tibial component of a remote TKA, for which the patient required emergent fasciotomies. Conclusions: Healthcare providers should be cognizant of potential orthopaedic hardware that can impede proper introduction of IO access.